PELATIHAN PENGGUNAAN MEDIA SOSIAL UNTUK MENINGKATKAN KINERJA PEMASARAN USAHA PEROBOT DI DESA RIDAN KECAMATAN BANGKINANG - Hasan, Samsurijal; Novita Sari, Efti; Aryadi; Aris Suhud (Jurnal Pengabdian Indonesia (JPI), 2025)
This training is based on the results of the analysis of the situation of blacksmiths (Rumbio Jaya Steel) Teratak Village, Rumbio Jaya District has not been professional in using social media to improve marketing performance. The target group in this service amounted to 150 people, namely the number of members of the Rumbio Jaya Steel cooperative. While the strategic targets in organizing this activity are 30 young men and women consisting of 18 young men and 12 young women who are sons and daughters of Rumbio Jaya Steel Cooperative Members. The implementation of this community service is carried out with steps: (1) Identification of potential; This activity is carried out in a participatory manner between the team and the target group aims to identify all the potential possessed by the target area; (2) Identification of opportunities based on the strength of the resources owned based on the results of identifying potential; (3) Determining the most popular platform; (4) Determining training needs; (5) Developing a training schedule; (6) Organizing training; and (7) Practice/simulation. activities carried out at the ONGA MAN Furniture Business Place in Ridan Permai Village, Bangkinang Kota District. As well as monitoring citizen responses through like, comment and share for 1 (one) week. The conclusion shows the low utilization of social media to promote products produced by furniture service businesses. In time, the production of these MSMEs can enter the popular Marketplace in Indonesia so that the volume of sales of marketing performance increases and the marketing reach is wider.